Prevalence, trends, outcomes, and disparities in hospitalizations for nonalcoholic fatty liver disease in the United States - Adejumo, Adeyinka Charles (Ann Gastroenterol, 2019)
BACKGROUND: As the frequency of nonalcoholic fatty liver disease (NAFLD) continues to rise in the United States (US) community, more patients are hospitalized with NAFLD. However, data on the prevalence and outcomes of hospitalizations with NAFLD are lacking. We investigated the prevalence, trends and outcomes of NAFLD hospitalizations in the US. METHODS: Hospitalizations with NAFLD were identified in the National Inpatient Sample (2007-2014) by their ICD-9-CM codes, and the prevalence and trends over an 8-year period were calculated among different demographic groups. After excluding other causes of liver disease among the NAFLD cohorts (n=210,660), the impact of sex, race and region on outcomes (mortality, discharge disposition, length of stay [LOS], and cost) were computed using generalized estimating equations (SAS 9.4). RESULTS: Admissions with NAFLD tripled from 2007-2014 at an average rate of 79/100,000 hospitalizations/year (P<0.0001), with a larger rate of increase among males vs. females (83/100,000 vs. 75/100,000), Hispanics vs. Whites vs. Blacks (107/100,000 vs. 80/100,000 vs. 48/100,000), and government-insured or uninsured patients vs. privately-insured (94/100,000 vs. 74/100,000). Males had higher mortality, LOS, and cost than females. Blacks had longer LOS and poorer discharge destination than Whites; while Hispanics and Asians incurred higher cost than Whites. Uninsured patients had higher mortality, longer LOS, and poorer discharge disposition than the privately-insured. CONCLUSIONS: Hospitalizations with NAFLD are rapidly increasing in the US, with a disproportionately higher burden among certain demographic groups. Measures are required to arrest this ominous trend and to eliminate the disparities in outcome among patients hospitalized with NAFLD.